Business Development Strategy With A Business Model Canvas Approach At Nh Studio In Sinjai Regency - Pahrul; Mariani Alimuddin (Association Of Indonesian Entrepreneurship Study Programs, 2024)
NH Studio faces significant challenges in achieving stability of its premises due to the inability to purchase a permanent location and the necessity of relying on annual rental contracts. To address this issue, NH Studio utilizes the Business Model Canvas with several transformations to maintain the existing business model and introduce new strategies. For long-term business development and sustainability, it is recommended to diversify services by offering equipment rental and conducting photography workshops. Through this diversification strategy, NH Studio can expand its service offerings, increase revenue, strengthen customer relationships, and establish itself as a comprehensive and reliable photography service provider. An analysis of the internal and external environment and the application of the Business Model Canvas are strategic steps in expanding the network and reaching more customers to face the intense competition in the photography industry.